MicroRNA-362-3p Inhibits Migration and Invasion via Targeting BCAP31 in Cervical Cancer - Yang, Shuya; Zhang, Xiyang; Sun, Yuanjie; Shi, Jingqi; Jiang, Dongbo; Wang, Jing; Liu, Yang; Hu, Chenchen; Pan, Jingyu; Zheng, Lianhe; Yang, Kun (Frontiers in Molecular Biosciences, 2020)
Cervical cancer (CC) is the most common malignant tumor in gynecology, and metastasis is an important cause of patient death. MiRNAs (microRNAs) have been found to play key roles in cervical cancer metastasis, but the effect of miR-362-3p in CC is unclear. This study aimed to investigate the role of miR-362-3p in cervical cancer migration and invasion. We compared the expression levels of miR-362-3p in cervical cancer tissues and adjacent normal cervical tissues. In CC tissues, miR-362-3p expression was significantly down-regulated, which is related to the cancer stage and patient survival. MiR-362-3p can effectively inhibit the migration and invasion of cervical cancer cells. The dual-luciferase reporter assay results showed that BCAP31 (B cell receptor associated protein 31) is a direct target protein of miR-362-3p. The results of the immunohistochemical examination of clinical tissue samples showed that BCAP31 was abnormally highly expressed in cervical cancer, which was positively correlated with the clinical stage. BCAP31 knockdown exerted similar effects as miR-362-3p overexpression. Further GSEA analysis showed that BCAP31 may participate in multiple biological processes such as protein transport, metabolism, and organelle organization. Our results suggest that miR-362-3p inhibits migration and invasion via directly targeting BCAP31 in cervical cancer, and restoring miR-362-3p levels may be a new treatment strategy for cervical cancer in the future.